Codewar: eksplorasi pengaturcaraan permainan digital - Harum, Norharyati (Penerbit UTeM Press, 2023)
Codewar 2021, a project organized by FTMK Universiti Teknikal Malaysia Melaka, showcased the talents of young programmers in creating digital games using Scratch programming software. This manuscript compiles the scientific writings of the participants, aiming to encourage students to deepen their knowledge of programming and promote STEM education. The manuscript also aims to attract students to participate in the next Codewar edition.